2022
DOI: 10.1038/s41528-022-00145-z
|View full text |Cite
|
Sign up to set email alerts
|

Large-area photonic lift-off process for flexible thin-film transistors

Abstract: Fabricating flexible electronics on plastic is often limited by the poor dimensional stability of polymer substrates. To mitigate, glass carriers are used during fabrication, but removing the plastic substrate from a carrier without damaging the electronics remains challenging. Here we utilize a large-area, high-throughput photonic lift-off (PLO) process to rapidly separate polymer films from rigid carriers. PLO uses a 150 µs pulse of broadband light from flashlamps to lift-off functional thin films from glass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…[ 78 ] To overcome these challenges, Weidling et al. [ 77 ] proposed a less complex and faster approach using a non‐laser Photonic Lift‐Off (PLO) that exposes a single pulse (150 µs of broadband light at 45 kW cm −2 ) onto the glass wafer. Before the flexible substrate is attached to the wafer, a light adsorbing layer (250 nm) is initially deposited onto the glass to reduce the incident lighting onto the polymer substrate, thus avoiding ashing.…”
Section: Flexible Substratesmentioning
confidence: 99%
“…[ 78 ] To overcome these challenges, Weidling et al. [ 77 ] proposed a less complex and faster approach using a non‐laser Photonic Lift‐Off (PLO) that exposes a single pulse (150 µs of broadband light at 45 kW cm −2 ) onto the glass wafer. Before the flexible substrate is attached to the wafer, a light adsorbing layer (250 nm) is initially deposited onto the glass to reduce the incident lighting onto the polymer substrate, thus avoiding ashing.…”
Section: Flexible Substratesmentioning
confidence: 99%
“…In this application, the ink used was disposed as a thin liquid film, the thickness of which was regulated by cylinders that provided a virtually unlimited ink supply, allowing for printing the ink at such high speeds in a roll-to-roll setup, demonstrating compatibility with current industrial fabrication techniques. The same principle can be applied for the commercial printing of flexible substrates, largely used in electronic devices, such as sensors [ 32 ], displays [ 33 ], electronic components [ 34 ], and solar cells [ 35 ], to name a few. In addition, it has been recently demonstrated that the printing of conductive inks via LIFT on paper can also be used for the fabrication of low-cost electronic devices [ 32 ].…”
Section: Industrial Perspectivesmentioning
confidence: 99%
“…It is worth mentioning that the responsive layer interface reaches 865 °C during the exfoliation process, while the top surface of PI is only 118 °C, which is enough to avoid thermal damage or feature degradation of the ultrathin device layer. [ 47 ] It is well known that temperature is one of the most important parameters to understand and describe photothermal processes. The simulation results show that the temperature of the exfoliated layer reaches thousands of Kelvin instantaneously under the laser irradiation, [ 20 ] which will cause the thermal damage to the device layer due to the instantaneous high temperature induced by the laser.…”
Section: Mechanisms Of Laser Lift‐off Technologiesmentioning
confidence: 99%
“…This photothermal effect inevitably causes the laser heat to diffuse around the ablated region through thermal conduction and thermal radiation. In general, the photothermal effect is mainly manifested in the three cases of using laser sources with long wavelength (i.e., visible or infrared band), [13] surface plasmon resonance, [46] and long pulse width (i.e., greater than electron-phonon relaxation time), [47] as the laser energy absorbed by the responsive material is converted into instantaneous localized heat, resulting in higher localized temperatures. As shown in Figure 4a-c, according to the principle of photothermal conversion, materials can be mainly divided into the following three categories: metals, carbon materials and semiconductors.…”
Section: The Mechanism Dominated By the Photothermal Effectmentioning
confidence: 99%